Charge matters: modulating secondary interactions in hyaluronan hydrogels - Mundinger, Patricia; Kupka, Julia Stefanie; Minsky, Burcu Baykal; Schädel, Nicole; Petri, Nadja; Laschat, Sabine; Böhm, Heike (ChemistrySelect, 2017)
Hyaluronic acid (HA) is a vital, functional component of the extracellular matrix (ECM). Following a synthetic biology approach, we designed polyelectrolyte hydrogels composed of HA as a polymeric backbone interconnected by short covalent crosslinkers. Utilizing a thiol-Michael addition, defined network structures are created, which can be modulated by the aromatic core and charge of the crosslinkers. With increasing negative network charge, varied both through the charge of the crosslinker and the degree of functionalization of the HA chain, the Young's modulus of the hydrogels decreases linearly as swelling ratios increase. Interestingly, secondary interactions with aromatic crosslinkers are stronger for elastin inspired crosslinkers with a pyridinium core compared to analogous triazolium crosslinkers. Based on the defined covalent interconnectivity of these HA-hydrogels, we were able to demonstrate the specific electrostatic and aromatic interactions induced by different short crosslinkers.
Gesehen am 17.08.2021